2020
DOI: 10.3390/pr8030344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrate and Perchlorate on Selenate Reduction in a Sequencing Batch Reactor

Abstract: Selenate removal from a water body is being vigorously debated owing to severe health impact, but inhibitions of coexisting anions have been reported. To suggest a viable treatment option, this study investigates the effect of nitrate and perchlorate on selenate reduction in a laboratory-scale sequencing batch reactor. The experimental design tests how competing electron acceptors (NO3− and ClO4−) and electron donor (acetate) limitations affect selenate reduction in the reactor. Results show that the reactor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…As a seed sludge, activated sludge was obtained from a local municipal wastewater treatment plant of I-city, South Korea. To prepare the inoculum of the FBBR, selenate reducing bacteria was selectively precultured before inoculation in a bench-scale sequencing batch reactor (SBR), following previous studies [11]. Under the anoxic condition, the acclimation period was maintained for more than a month.…”
Section: Inoculum and Culture Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…As a seed sludge, activated sludge was obtained from a local municipal wastewater treatment plant of I-city, South Korea. To prepare the inoculum of the FBBR, selenate reducing bacteria was selectively precultured before inoculation in a bench-scale sequencing batch reactor (SBR), following previous studies [11]. Under the anoxic condition, the acclimation period was maintained for more than a month.…”
Section: Inoculum and Culture Mediamentioning
confidence: 99%
“…Previous research demonstrated simultaneous bioreduction of selenate and nitrate in sequencing batch reactors cultivating acclimated selenate-reducing bacteria [11]. To reduce selenate at very low concentrations, a fixed-bed biofilm reactor (FBBR) might be more suitable from the engineering point of view than a suspended growth reactor because it is designed to prevent microbial washout while keeping the biocatalysts, i.e., selenate reducing bacteria, in the system longer.…”
Section: Introductionmentioning
confidence: 99%
“…The initial selenate and nitrate concentrations were 0.1 mM and 0.96 mM NO 3 − -N, respectively. For that study, acetate was the electron donor, and seed sludge was activated sludge from a wastewater treatment plant [12]. However, most biological selenium reduction experiments have been limited to either pure culture or anaerobic sludge blanket methods.…”
Section: Introductionmentioning
confidence: 99%
“…However, most biological selenium reduction experiments have been limited to either pure culture or anaerobic sludge blanket methods. A relatively limited number of studies are available with a mixed microbial community and competitive anions [7,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of nitrate and perchlorate on selenate reduction in a batch reactor was investigated by Kim et al [5]. They selectively enriched selenate-reducing bacteria in bench-scale sequencing batch reactors, which were seeded with activated sludge, and operated them semi-continuously in parallel for more than one and a half months.…”
mentioning
confidence: 99%